Penyuluhan Penggunaan Gawai Untuk Mencegah Gangguan Belajar Pada Siswa - Aster Pujaning Ati; Harmi Ibnu Dja’far; Mu’thia Mubasyira; Lusiana Wulansari; Loecita Sandiar; Sigit Widiyarto (Jurnal Pengabdian UntukMu NegeRI, 2022)
The use of gadgets will have a serious impact on children's learning disorders. In another study, it was revealed that excessive use of gadgets can cause health problems. Learning disorders will be seen when all learning obligations are gradually neglected. The role of parents and teachers is very important in preventing children's learning disorders. Likewise, disturbances in children's health, which can occur at any time. The implementation of community service activities was held at SMP Alikhlas Bekasi. The implementation method used is FGD, participatory and practical. This activity was attended by 50 seventh grade junior high school students for the 2019/2020 academic year. The results of the activity showed that the results of the oral evaluation were 71, while the written evaluation was 80. The students already understood the impact of excessive use of gadgets. Keywords: Counseling, Devices, Middle School Students